The Impact of Transformational Leadership on Employee Performance in Three Star Hotels: The Mediating Role of Job Satisfaction - Yulianti, Emma; Isgiarto, Restu (Journal of Applied Business, Taxation and Economics Research, 2025)
This study aims to examine the effect of transformational leadership on employee performance, both directly and indirectly through job satisfaction mediation among hotel employees in East Java. The research population consists of 3-star hotel employees in East Java. The sample was determined using the purposive sampling method. Data were collected through a survey technique and analyzed using Structural Equation Modeling with WarPLS 7 .0. The results show that transformational leadership significantly influences employee performance both directly and indirectly, through job satisfaction mediation, among 3-star hotel employees in East Java. This study offers a theoretical contribution to the applicability of Social Exchange Theory (SET) and practical implications, suggesting that managers need to be equipped with transformational leadership skills to improve employee performance.